The transformation of American international power in the 1970s - Zanchetta, Barbara, 1976- (New York : Cambridge University Press, 2014)
"Barbara Zanchetta analyzes the evolution of American-Soviet relations during the 1970s, from the rise of detente during the Nixon administration to the policy's crisis and fall during the final years of the Carter presidency. This study traces lines of continuity among the Nixon, Ford and Carter administrations and assesses its effects on the ongoing redefinition of America's international role in the post-Vietnam era. Against the background of superpower cooperation in arms control, Dr Zanchetta analyzes aspects of the global bipolar competition, including US-China relations, the turmoil in Iran and Afghanistan, and the crises in Angola and the Horn of Africa. In doing so, she unveils both the successful transformation of American international power during the 1970s and its long-term problematic legacy"--
Machine generated contents note: Introduction; Part I. The Remaking of American Global Power, 1969-1976: 1. The Nixon administration and a 'moment of beginning'; 2. The diplomatic revolution: the China opening; 3. An 'era of negotiation' versus the 'supreme test': Nixon between SALT I and Vietnam; 4. 'Protect me': Nixon and the Shah of Iran; 5. De;tente questioned: domestic challenges and international crisis; 6. The Ford (and Kissinger) administration; 7. Defending the dual track: SALT II, Angola, and the crisis of de;tente; Part II. Rethinking the Fall of Detente, 1977-1980: 8. The Carter administration's ambitious agenda; 9. Initial shift: the Horn of Africa; 10. Recreating the strategic triangle: normalization with China and SALT II; 11. The loss of Iran; 12. Reaffirming containment: the Carter doctrine; Conclusion.
Includes bibliographical references (pages 315-324) and index.
Keywords: POLITICAL SCIENCE / International Relations / General; United States -- Foreign relations -- 1969-1974.; United States -- Foreign relations -- 1974-1977.; United States -- Foreign relations -- 1977-1981.; United States -- Foreign relations -- Soviet Union -- History; Soviet Union -- Foreign relations -- United States -- History